2020
DOI: 10.1111/1750-3841.15026
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of green tea (Camellia sinensis) by wine yeast Saccharomyces cerevisiae

Abstract: Wine yeast Saccharomyces cerevisiae 71B was used in fermentation of green tea to modulate the volatiles and nonvolatiles. After fermentation, higher alcohols, esters, and acids, such as isoamyl alcohol, isobutanol, ethyl octanoate, ethyl decanoate, octanoic, and decanoic acids were generated. Some key aroma compounds of tea including linalool, hotrienol, dihydroactinidiolide, and 2-phenylethanol increased significantly. Among these compounds, linalool and 2-phenylethanol increased by 1.3-and 10-fold, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 49 publications
(58 reference statements)
3
2
0
Order By: Relevance
“…The reason for the decline of antioxidant activities may be that some antioxidant substances, such as tea polyphenols, were degraded in tea wine fermentation. Similar results were reported in previous research ( 31 , 32 ).…”
Section: Resultssupporting
confidence: 93%
“…The reason for the decline of antioxidant activities may be that some antioxidant substances, such as tea polyphenols, were degraded in tea wine fermentation. Similar results were reported in previous research ( 31 , 32 ).…”
Section: Resultssupporting
confidence: 93%
“…Dzialo et al [ 62 ] suggested isoamyl alcohol and 2-phenylethanol were the major fuel alcohols found in alcoholic beverages. In this study, MF-broth fermentation revealed the presence of isoamyl alcohol and 2-phenylethanol, with alcohol produced at a higher level in both the SF and CF with S. cerevisiae TISTR 5088 and W. anomalus P2, which was consistent with previous studies [ 34 , 36 , 43 , 65 ]. However, although in the original MF-broth, a high quantity of (Z)-3-hexen-1-ol and benzyl alcohol (known as tea leaf alcohol) was found, after fermentation that compound was reduced by the yeast [ 66 ].…”
Section: Resultssupporting
confidence: 93%
“…From these studies, non- Saccharomyces yeasts were recognized for their low ethanol fermentation rate, in comparison to S. cerevisiae . W. anomalus has previously been investigated in the production of low alcohol with high levels of esters, such as in kiwi wine [ 34 ], muscat bailey wine [ 13 ], apple wine [ 35 ] and Baijiu [ 36 ]. The members of the genus Cyberlindnera , as well as C. subsufficiens , C. mrakii , C. jadinii , C. fabianii and C. saturnus [ 9 , 37 , 38 , 39 ] were studied on the generation of a fruity aroma in non-alcoholic beer, but C. rhodanensis has not been reported for use in fermented beverages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the UPLC-Q-TOF-MS analysis, the glycoside of 2-phenylethanol (2-phenylethyl-6-O-β-D-xylopyranosyl- β-D-glucopyranoside) was also found ( Fig. 3 ), which further verified the results discussed in our previous study that the key flavor compound 2-phenylethanol was not only from phenylalanine metabolism but also from glycoside precursor hydrolysis ( Wang et al, 2020 ).
Fig.
…”
Section: Resultssupporting
confidence: 88%